Spatial Mapping of Coconut Plantation in Airmadidi District, North Sulawesi Using Geographical Information System - Rotinsulu, Wiske; Margaretha, Geby; Pakasi, Sandra (ITScience (Information Technology and Science), 2023)
Coconut (Cocos nucifera L.) known by many as the